Evidence for asynchronism in the magnetic cataclysmic variable EU UMa (RE1149+28) - Somov, N. N.; Somova, T. A.; Bonnet-Bidaud, J. M.; Mouchet, M. (Одеські астрономічні публікації, 2017)
We present the results of optical time-resolved spectroscopy of the magnetic cataclysmic variable EU UMA (RE1149-i-28), which were obtained with the scanner of the 6 m telescope on April 3 and 4, 1994. Analysis of the behaviour of the parameters of Balmer and Hell emission lines in the spectra of EU UMA has revealed the following: -dips in the equivalent widths of the lines repeatable with the orbital period. Considering the dips as a result of eclipse of the most part of the accretion stream by the secondary we have improved the value of the orbital period as 90.1441 :I:0.0007min and have estimated the inclination of the system to be % 70°; in addition to radial velocity variations over the orbital period the oscillations with the period of 45-min and 37-min of the velocities of the centers of gravity and the peak of the lines, respectively. We associate the 45 min oscillations with the radiation from the accretion curtain or the beginning of the magnetic part of accretion stream and the 37 min variations with the radiation from the strong resonance magnetic fields which was observed as the monochromatic pulsations in the spectra of intermediate polars (Somov et al.,1997, 1998a,1998b, 20002001). The presence of 45-min oscillations is an argument in favor of diskless accretion in the system. The 37-min variations point to asynchronous rotation of the white dwarf over the Spin period % 74 min. The spectral light curves (integrated flux in the range of wavelengths 4000-5000 A) have shown significant changes of the mean fluxes (% 4 times) and of the composition of quasi-periodic oscillations in the range of periods 20-120 min on a time-scale of 1 day. In the high state of brightness on April 3, 1994 the spectral light curve showed a hump which corresponds to the longitude of the accretion spot of 45°in the standard model of polars. In the low accretion state on April 4, 1994 the spectral light curve showed a step-like jump when the mean brightness of the object increased % 2 times. Such a behaviour of the system can be the result of the change of the magnetic part of accretion trajectory due to the asynchronism. We found a relationship between the jump of brightness and the jump of the phase and amplitude of the 37-min oscillations. On the basis of all the detected properties we conclude that the system is an asynchronous magnetic rotator With a polar-like magnetic field and With the magnetic and rotation poles close to each other.